Atypical stab injury suggesting ritual suicide - Kučerová, Štěpánka; Vojtíšek, Tomáš; Hejna, Petr (Archiwum medycyny sadowej i kryminologii, 2016)
Sharp weapons have been one of the most common deadly tools in cases of homicide and suicide for a long time. Tentative incisions accompany the majority of suicides by sharp force and the absence of hesitation marks provokes questions about the manner of death. We present the bizarre fatality of a 41-year-old male with an isolated circumscribed incision on the right neck, where the body was found lying in a pool of blood in the shower of his apartment. The internal examination revealed a 4-cm-long channel-like defect running inwardly and downwardly along the right sternocleidomastoid region. The cause of death was external bleeding from an injured right carotid artery and internal jugular vein. The wound had clean non-contused margins without any conspicuous hesitation injuries. A fragment of a razor blade, found in blood splatters, was identified as the only potential injuring tool. The case was classified as a suicide.
Keywords: dospělí; Suicide; bodné rány; Self Mutilation; Cause of Death; Adult; Neck Injuries; autopsy; sebepoškozování; lidé; Vascular System Injuries; rituální chování; poranění cév; sebevražda; Wounds, Stab; ritual suicide; poranění krku; hesitation marks; Male; razor blade; Ceremonial Behavior; stab wound; mužské pohlaví; příčina smrti; Humans